Global diversity and distribution of aerobic anoxygenic phototrophs in the tropical and subtropical oceans. (27th January 2022) - Gazulla, Carlota R.; Auladell, Adrià; Ruiz‐González, Clara; Junger, Pedro C.; Royo‐Llonch, Marta; Duarte, Carlos M.; Gasol, Josep M.; Sánchez, Olga; Ferrera, Isabel
Summary: The aerobic anoxygenic phototrophic (AAP) bacteria are common in most marine environments but their global diversity and biogeography remain poorly characterized. Here, we analyzed AAP communities across 113 globally‐distributed surface ocean stations sampled during the Malaspina Expedition in the tropical and subtropical ocean. By means of amplicon sequencing of the puf M gene, a genetic marker for this functional group, we show that AAP communities along the surface ocean were mainly composed of members of the Halieaceae (Gammaproteobacteria), which were adapted to a large range of environmental conditions, and of different clades of the Alphaproteobacteria, which seemed to dominate under particular circumstances, such as in the oligotrophic gyres. AAP taxa were spatially structured within each of the studied oceans, with communities from adjacent stations sharing more taxonomic similarities. AAP communities were composed of a large pool of rare members and several habitat specialists. When compared to the surface ocean prokaryotic and picoeukaryotic communities, it appears that AAP communities display an idiosyncratic global biogeographical pattern, dominated by selection processes and less influenced by dispersal limitation. Our study contributes to the understanding of how AAP communities are distributed in the horizontal dimension and the mechanisms underlying their distribution across the global surface ocean.